2011
DOI: 10.1080/20932685.2011.10593090
|View full text |Cite
|
Sign up to set email alerts
|

Putting Assumed Emotion in Fashion Brand Literacy: Understanding Brand-Identity Relationship in the Interdependent Asian Context

Abstract: Over the past decade, consumer researchers have been interested in understanding symbolic relationship between consumers and brands, especially on identity construction (Elliott & Wattanasuwan, 1998;Escalas & Bettman, 2005;Kirmani, 2009) and its implications on brand management (Arvidsson, 2005;Holt, 2002;. Following a cultural-psychological view to study how culture shapes brand-identity relationship, Eckhardt (2000) addresses that little attention have been paid to understand consumer behavior within interde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This also echoed the ‘fitting in’ vs. ‘standing out’ debate that Griffiths () presented. In other words, in the view of the status matchers that took part in the present study, a person's consumption choices should align with his/her social position to meet the social expectations (Jiang & Cova, ; Lam, Liu, & To, ). For these participants, the primary ethical concern in buying counterfeits was not the issue of disrespecting the original design or violating intellectual property rights, but the extent to which the social group to which they belonged had the same understanding of the brand.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This also echoed the ‘fitting in’ vs. ‘standing out’ debate that Griffiths () presented. In other words, in the view of the status matchers that took part in the present study, a person's consumption choices should align with his/her social position to meet the social expectations (Jiang & Cova, ; Lam, Liu, & To, ). For these participants, the primary ethical concern in buying counterfeits was not the issue of disrespecting the original design or violating intellectual property rights, but the extent to which the social group to which they belonged had the same understanding of the brand.…”
Section: Resultsmentioning
confidence: 98%
“…Her perception of counterfeiting was primarily based on her views of how a student should behave and dress. Lam et al () argued that the values and responsibilities associated with the social identities can become a force that legitimizes consumption habits, the way that people dress and what they use. Yet, our findings revealed that consumers appropriate these cultural values in their consumption of counterfeits as ‘ethical’ behaviour in the Chinese cultural context.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas Chinese tend to seek relaxation and shopping more when traveling, Russians tend to seek physical activities and learning new knowledge/culture when traveling. Possessing different travel intentions is in line with previous research, which showed that tourists of different nationalities behave in different ways (Cho, 1991;Lam, Liu, & To, 2011). Further analysis was performed regarding differences between the countries' structural models.…”
Section: Structural Equation Model Analysismentioning
confidence: 83%
“…India is a country of diverse cultures, in terms of people following different religions and speaking languages that can change every 20 miles; diversified cultures lead to different tastes, habits and preferences, and hence the motivations of mall shopping behavior may differ markedly from those of consumers in other countries (Devgan & Kaur, 2010). Additionally, as suggested by Lam, Liu, and To (2011), there exist clear cultural differences between the localities within metropolitan and nonmetropolitan cities, and hence the variables measured in this study reflect both the cultural phenomenon and often used variables in studies that examine consumer behavior with respect to purchase intention.…”
Section: Study Variables and Hypothesis Developmentmentioning
confidence: 97%